Variability in donor selection among pediatric heart transplant providers: Results from an international survey. (13th May 2019) - Godown, Justin; Kirk, Richard; Joong, Anna; Lal, Ashwin K.; McCulloch, Michael; Peng, David M.; Scheel, Janet; Davies, Ryan R.; Dipchand, Anne I.; Miera, Oliver; Gossett, Jeffrey G.
Abstract: There is considerable variability in donor acceptance practices among adult heart transplant providers; however, pediatric data are lacking. The aim of this study was to assess donor acceptance practices among pediatric heart transplant professionals. The authors generated a survey to investigate clinicians' donor acceptance practices. This survey was distributed to all members of the ISHLT Pediatric Council in April 2018. A total of 130 providers responded from 17 different countries. There was a wide range of acceptable criteria for potential donors. These included optimal donor‐to‐recipient weight ratio (lower limit: 50%‐150%, upper limit: 120%‐350%), maximum donor age (25‐75 years), and minimum acceptable left ventricular EF (30%‐60%). Non‐US centers demonstrated less restrictive donor selection criteria and were willing to accept older donors (50 vs 35 years, P  < 0.001), greater size discrepancy (upper limit weight ratio 250% vs 200%, P  = 0.009), and donors with a lower EF (45% vs 50%, P  < 0.001). Recipient factors were most influential in the decision to accept marginal donors including recipients requiring ECMO support, ventilator support, and highly sensitized patients with a negative XM. However, programmatic factors impacted the decision to decline marginal donors including recent programmatic mortalities and concerns for programmatic restrictions from regulatory bodies. There is significant variation in donor acceptance practices among pediatric heart transplant professionals. Standardization of donor acceptance practices through the development of a consensus statement may help to improve donor utilization and reduce waitlist mortality.